Pengaruh Media Kartu Pintar Alfabet Terhadap Kemampuan Literasi Awal Anak Usia 5-6 Tahun Di Tk Aisyiyah Bustanul Athfal Muara Tembesi - Eliza, Nova; Indryani; Rizki Surya Amanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low early literacy skills of children aged 5–6 years at TK Aisyiyah Bustanul Athfal Muara Tembesi. The problems identified include children’s difficulties in recognizing alphabet letters, distinguishing vowels and consonants, and grouping letters based on their shapes and sounds. This study aims to determine the effect of using alphabet smart card media on early childhood literacy skills.This research employed a quantitative approach using a pre-experimental method with a one group pretest-posttest design. The sample consisted of 18 children in group B. Data were collected using an observation sheet that had been tested for validity. Data analysis techniques included normality test, homogeneity test, and hypothesis testing using paired sample t-test.The results showed a significant effect of the use of alphabet smart card media on children’s early literacy skills. This was indicated by the t-value of 48.089 with a significance value (Sig. 2-tailed) of 0.000 < 0.05, meaning that Ha was accepted and Ho was rejected. Furthermore, the effect size calculated using Cohen’s d was 1.13, which falls into the strong effect category.In conclusion, alphabet smart card media is effective in improving early literacy skills in children aged 5–6 years. This media can serve as an engaging and innovative learning tool to support early childhood literacy development.